Perbaikan Tcp Westwood + - Sukiswo, Sukiswo (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
TCP Westwood+ isÂ evolution of TCP Westood. TCP Westwood+ representing one of TCP proposed for the modification of existing TCP now. Specially TCP Westwood+, TCP Westwood+ sender keeps an end to end bandwidth estimation to adjust the smart transmission rate after detection a packet loss. In this way , TCP Westwood+ can improve; repair the standard TCP (Newreno, SACK) in a lossy environment. This paper comment the mechanism congestion base control TCP Westwood+, testing performance of TCP Westwood+, enhance TCP Westwood+ by modification increase phase from additive mechanism to multiplicative mechanism, and compare with TCP Westwood+ standard.Keywords: TCP Westwood+, end to end bandwidthÂ estimation, estimation filter, additive mechanism,Â multiplicative mechanism